An art of porcelain painting in aspects of the professional socialization - Brants, Inese (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
This report will take a brief look at socio-economic relation between porcelain painting artists, producers and consumers. The author will be drawing from the author’s experience gained in the visiting and resident time in more than 10 European porcelain factories, collaboration with Art universities, leading the Porcelain painting workshops at International Art Teacher and Porcelain Painting Symposia in Latvia and abroad. Personal experience and studying of International Porcelain painters organization home pages and over 100 china painters websites made it possible to analyze and compare the possibility of vocational training, the artist's creative career opportunities, professional literature and the membership in the professional organizations and institutions. Porcelain painting art is ceramic technology – based result of individual creativity. The socio-economic relation interaction between artist, producer and consumer marked historically important stages of development of the porcelain painting art. The education plays the crucial importance on the social integration processes of artist. The professional stratification and integration process realizes in the there distinct and isolated groups of porcelain painters – 1. An artists integrated in the porcelain industry. 2. An artists integrated in the ceramic art structures. 3. Artists integrated in the china painters organized structures. Balance between self-expression needs and material needs of the individual artist inability to self-realization problems. Internal needs depended on the artist as creative personality viability in porcelain factory. The opportunity to create personal studio contribute to the development of porcelain painting art, but the artist does not guarantee the competitiveness of the market and material support to the existence. The need to ensure the existence powered of professional socialization processes that result in porcelain painting artists replace existing or fit into other professional and public bodies. Latvia has its own tradition of porcelain art and great artists, but their creative potential sales opportunities in today's socio-economic conditions have not been investigated. In Latvia no more exist first group – in porcelain industry integrated artists, because porcelain industry no more existed. The third group, have not developed because the Latvian artists are not integrated into the International World China Painters organizations. In Latvia Porcelain painting as a hobby art are not very popular, so the knowledge and skills of porcelain painting is not yet a product of the request. The author reveals the socio-economic stratification of professional interaction – induced effects on an artist's creative performance and points to the social background to create a typology of porcelain painting art objects.